Manufacturing planning and control for supply chain management - Jacobs, F. Robert (McGraw-Hill/Irwin, 2011)
Improve supply chain effectiveness, productivity, customer satisfaction, and profitability with help from this authoritative resource. Completely up-to-date, Manufacturing Planning and Control for Supply Chain Management: APICS/CPIM Certification Edition offers comprehensive preparation for the challenging CPIM exam with hundreds of practice exam questions and detailed case studies. In-depth coverage of manufacturing planning and control (MPC) best practices and the latest research gives you the competitive advantage in today's global manufacturing environment, and helps you to obtain the coveted CPIM designation. Covers the state of the art in manufacturing, including: -- Manufacturing planning and control -- Enterprise resource planning -- Demand management -- Forecasting -- Sales and operations planning -- Master production scheduling -- Material requirements planning -- Production activity control -- Advanced scheduling -- Just-in-time -- Distribution requirements planning -- Management of supply chain logistics -- Order point inventory control methods -- Strategy and MPC system design